Vulnerability zoning of urban areas against earthquake (case study: Urmia city) - Farahmand, Ghasem; Samet, Komeil; Golmohammadi, Hassan; Patel, Nilanchal (Geodesy and Cartography, 2022)
The danger of earthquake always overshadows human societies and causes irreparable damage to these societies; therefore, preparedness to deal with this crisis by identifying vulnerability points and removing them is effective in reducing the damages caused by earthquake. Due to the location of Iran on one of the two world’s earthquake belts and the existence of many faults, the occurrence of earthquakes on the plateau of Iran is a natural phenomenon. Iran is one of the ten earthquake-prone countries in the world. Consequently, the city of Urmia is no exception to this rule due to its location in the hillsides of the Zagros Mountains and witnesses a large number of earthquakes with different intensities every year. Therefore, to deal with the above problem, we need more detailed studies in the fields of construction and safety. In this study, in order to evaluate the severity of earthquake vulnerability, effective parameters were identified and weighted using fuzzy hierarchical analysis process. Vulnerability maps were prepared by index overlap method and fuzzy logic, for statistical blocks of Urmia city and were presented visually in spatial information system. The results showed that about 50% of the city is vulnerable to earthquakes; to be more precise, about 151574 square meters, i.e. 0.005% has a very high degree of vulnerability and 11538359 square meters, with a percentage of 0.40%, has a high degree of vulnerability to earthquakes.